Analisis Load Balancing Pada Web Server Menggunakan Algoritme Weighted Least Connection - Dany Rahmana; Rakhmadhany Primananda; Widhi Yahya (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Load balancing is a technique to divide the workload on 2 or more servers when there is a request from the client. In load balancing techniques there are several algorithms,, others: least connection, weighted least connection and others. This research uses weighted least connection algorithm. The weighted least connection algorithm divides the server load based on the weight value. The supporting tool for load balancing is IPVSADM with Piranha interface. In the test, the measured parameters are throughput, response time and CPU usage. The tool used in the test in httperf. From the test results with delivery of 10000 connections obtained by sending connections per second more will increase the throughput value. On testing the highest throughput value is 547,74 KB / s. Compared with the response time response, if given a high connection will be higher in the sense of slowing down. In connection distribution testing, the server with the highest weights accommodates more connections of 4000 connections, the lowest weight of 1000 connections from the total 10000 connections. In CPU usage testing, the weighted least connection algorithm is at least better than the least connection algorithm when applied to a heterogeneous server.